Influence of gum-chewing on postoperative bowel activity after laparoscopic surgery for gastric cancer: A randomized controlled trial. Issue 13 (March 2017) - Ge, Bujun; Zhao, Hongmei; Lin, Rui; Wang, Jialiang; Chen, Quanning; Liu, Liming; Huang, Qi
Abstract: Background: In some studies, gum-chewing was demonstrated to have a beneficial effect on resumption of bowel function; however, other contradictory findings in other studies refute the effects of gum-chewing on peristaltic movements and digestive system stimulation. In addition, most previous studies were after colorectal or gynecology surgery, whereas few reports focused on the effect of gum-chewing after gastrectomy. The aim of this randomized controlled trial was to assess the effectiveness of gum-chewing on postoperative bowel function in patients who had undergone laparoscopic gastrectomy. Methods: From March 2014 to March 2016, 75 patients with gastric cancer received elective laparoscopic surgery in Shanghai Tongji hospital and were postoperatively randomly divided into 2 groups: 38 in a gum-chewing (Gum) group and 37 in a control (No gum) group. The patients in the Gum group chewed sugarless gum 3 times daily, each time for at least 15 minutes, until the day of postoperative exhaust defecation. Results: The mean time to first flatus (83.4 ± 35.6 vs. 79.2 ± 24.2 hours; P  = 0.554) and the mean time to first defecation (125.7 ± 41.2 vs. 115.4 ± 34.2 hours; P  = 0.192) were no different between the no gum and Gum groups. There was also no significant difference in the incidence of postoperative ileus ( P  = 0.896) and postoperative hospital stay ( P  = 0.109) between the 2 groups. The postoperative pain score at 48 hours ( P  = 0.032) in the Gum group was significantly higher than in the no gum group. There was no significant difference between the 2 groups in regards to patient demographics, comorbidities, duration of surgery, complications, and nausea/vomiting score. Conclusion: Gum-chewing after laparoscopic gastrectomy did not hasten the return of gastrointestinal function. In addition, gum-chewing may increase patient pain on the second postoperative day.